A Comparative Analysis by Experimental Investigations on Normal and Ground Ultrafine Mineral Admixtures in Arresting Permeation in High-Strength Concrete - Jain, Neelamani; Mishra, Ragini; Raj, Ravindra (International Journal of Scientific Research in Civil Engineering, 2022)
In this growing world there has always been a strong competition in the market amongst industries in term of economy, profits, shares etc. one such industry is construction industry where concrete is the key building substance which is in limelight. Since past, we have seen much advancement in concrete because of the research which is in progress on concrete to come out with a product which should be economical and strong enough to resist all kind of loads. In this thesis, fly ash and silica fume are used as a replacement for cement along with steel fibers by volume of concrete. Here, fly ash is replaced by 0%, 15%, 30% and silica fume is replaced by 0%, 6%, 12% and 18% for cement. Initially, a set of concrete specimens were casted with 0%, 15%, 30% fly ash and 0%, 6%, 12% and 18% silica fume with 0% addition of steel fibers and tested for compressive, flexural and split tensile strength. Secondly, another set of concrete specimens were casted with 0%, 15%, 30% fly ash and 0%, 6%, 12% and 18% silica fume with 0.5% addition of steel fibers and tested for the same. Similarly, another set of samples were casted 0%, 15%, 30% fly ash and 0%, 6%, 12% and 18% silica fume with 1% addition of steel fibers and tested to determine the mechanical properties of concrete. And it was observed that maximum compressive, flexural and split tensile strength was attained at 15% fly ash and 12% silica fume with 1% steel fiber.
Keywords: Silica Fume; Fly Ash; Compressive Strength; Flexural Strength; Split Tensile Strength